Green Human Resource Management (GHRM) and Environmental Performance in Pakistani Hotel Industry: The Role of Green Perceived Organizational Support (POS), Pro-Environmental Behavior and Green Innovative Work Behavior (GIWB) - Meraj, Rabia; Nasir, Sobia; Shafqat, Amna; Indrees, Sadia (Pakistan Journal of Humanities and Social Sciences, 2023)
The aim of this research is to examine the effect of GHRM practices on hotel environmental performance in Pakistan. The study further analyze the effects of green POS, pro-environmental behavior, or green innovative work behavior (GIWB). The target area was belong of five-star hotel workers in Pakistan. PLS-SEM was used to analyse data gathered by a survey questionnaire from 225 workers. According to the findings green POS, which leads to pro-environmental behavior and GIWB, was establish to be a powerful predictor of GHRM practices (green recruitment or hiring, green training, green rewarding, or green performance assessment). The results also revealed that pro-environmental behavior or GIWB had a momentous effect on hotel environmental performance. Moreover, Green HRM practices are considered to indirectly contribute to environmental performance via green POS, pro-environmental behavior, and GIWB. This research is one of the unique efforts in the area of environmental management to incorporate GHRM practices with green POS, pro-environmental behaviors, and GIWB. It makes a clear contribution towards a new streamline of research to realize the critical function of GHRM exercise to modify the environmental performance in hotels. The research aggregation have suggested GHRM is an important indication for supporting green POS and encouraging pro-environmental behaviors, as well as GIWB. It can support hotel managers to promote the green POS among the employees by practicing the GHRM practices that enables pro-environmental behavior and GIWB to solve the hotel industry's increasing environmental problems. Recent research suggests that managers should maintain and follow GHRM efforts and policies to improve environmental performance.